Renal Endothelial Cell‐Targeted Extracellular Vesicles Protect the Kidney from Ischemic Injury. Issue 3 (23rd November 2022) - Zhang, Kaiyue; Li, Rongrong; Chen, Xiaoniao; Yan, Hongyu; Li, Huifang; Zhao, Xiaotong; Huang, Haoyan; Chen, Shang; Liu, Yue; Wang, Kai; Han, Zhibo; Han, Zhong‐Chao; et al.
Abstract: Endothelial cell injury plays a critical part in ischemic acute kidney injury (AKI) and participates in the progression of AKI. Targeting renal endothelial cell therapy may ameliorate vascular injury and further improve the prognosis of ischemic AKI. Here, P‐selectin as a biomarker of ischemic AKI in endothelial cells is identified and P‐selectin binding peptide (PBP)‐engineered extracellular vesicles (PBP‐EVs) with imaging and therapeutic functions are developed. The results show that PBP‐EVs exhibit a selective targeting tendency to injured kidneys, while providing spatiotemporal information for the early diagnosis of AKI by quantifying the expression of P‐selectin in the kidneys by molecular imaging. Meanwhile, PBP‐EVs reveal superior nephroprotective functions in the promotion of renal repair and inhibition of fibrosis by alleviating inflammatory infiltration, improving reparative angiogenesis, and ameliorating maladaptive repair of the renal parenchyma. In conclusion, PBP‐EVs, as an ischemic AKI theranostic system that is designed in this study, provide a spatiotemporal diagnosis in the early stages of AKI to help guide personalized therapy and exhibit superior nephroprotective effects, offering proof‐of‐concept data to design EV‐based theranostic strategies to promote renal recovery and further improve long‐term outcomes following AKI. Abstract : Endothelial cell (EC) injury is one of the specific features of acute kidney injury (AKI). However, there is no feasible target or effective theranostic strategy for EC‐targeted AKI treatment. In the present study, the authors identify P‐selectin as a biomarker of ischemic AKI and develop P‐selectin binding peptide (PBP)‐engineered extracellular vesicles with imaging and therapeutic functions for the first time.